Pengaruh Pelayanan dan Kemudahan Bertransaksi Menggunakan Bank Digital (Seabank) terhadap Minat Menabung Mahasiswa Jurusan PBS - Wiyono, M. Raka Puguh; Putri, Wafie Rafiqoh Supena; Handayani, Shabilla Putri; Hidayat, Wahyu; Ibrahim, Zaini (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Modern technology advances both quickly and slowly these days. One significant function of technology is to facilitate people's access to the resources they require. individuals's lives nowadays are shaped by technology advancements; the pace at which these advancements occur, both in terms of the internet and devices, is what matters most since it encourages individuals to engage in networked activities, including using digital banking. The benefits of digital banks include fund storage and cashless transaction capabilities, or non-cash payments. One example of how technology is evolving and keeping up with the times is Seabank.